2017
DOI: 10.1021/acsmedchemlett.7b00172
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of the First c-Met/HDAC Inhibitors Based on Pyridazinone Derivatives

Abstract: Simultaneous blockade of more than one pathway is considered to be a promising approach to overcome the low efficacy and acquired resistance of cancer therapies. Thus, a novel series of c-Met/HDAC bifunctional inhibitors was designed and synthesized by merging pharmacophores of c-Met and HDAC inhibitors. The most potent compound, , inhibited c-Met kinase and HDAC1, with IC values of 0.71 and 38 nM, respectively, and showed efficient antiproliferative activities against both EBC-1 and HCT-116 cells with greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Small molecules capable of inhibiting multiple targets provide an attractive alternative since the toxicity, route of delivery, and pharmacodynamic and pharmacokinetic properties need only be optimized for a single drug. Indeed, recent studies point to the therapeutic potential of fusion compounds designed to inhibit multiple targets such as HDAC inhibitors fused with either phosphatidylinositol 3-kinase (Qian et al, 2012) or cMET inhibitors (Lu et al, 2017). Our study adds to this growing list of examples where bifunctional compounds may provide superior efficacies at reducing cancer growth as opposed to single agents.…”
Section: Discussionmentioning
confidence: 82%
“…Small molecules capable of inhibiting multiple targets provide an attractive alternative since the toxicity, route of delivery, and pharmacodynamic and pharmacokinetic properties need only be optimized for a single drug. Indeed, recent studies point to the therapeutic potential of fusion compounds designed to inhibit multiple targets such as HDAC inhibitors fused with either phosphatidylinositol 3-kinase (Qian et al, 2012) or cMET inhibitors (Lu et al, 2017). Our study adds to this growing list of examples where bifunctional compounds may provide superior efficacies at reducing cancer growth as opposed to single agents.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, many literatures have focused on the design and synthesis of pyridazinone derivatives to develop new compounds with higher anti-cancer efficacy and verify the potential specific target [ 19 21 ]. Some studies have demonstrated that their specific mechanisms are acting as the inhibitors for important tumor targets such as p38, PFKFB3, PARP-1, C-Met or C-Met/HDAC [ 22 27 ]. The other bioactive moiety in the molecular structure of IMB5043 is a thiophene ring which occurs in many drugs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuing the development of RTK/HDAC dual inhibitors, in 2017, Lu et al reported the first example to target the RTK c-Met [ 86 ]. Herein, a selective c-Met inhibitor was fused with HDAC inhibitor pharmacophores to afford a series of hybrid molecules.…”
Section: Class-i Hdac Dual Inhibitorsmentioning
confidence: 99%